Avaliação de 5 tipos de fixação da osteotomia sagital dos ramos mandibulares em grandes avanços com rotação anti-horária: uma análise de elementos finitos - Mendes, Gabriel Cury Batista (2018)
The aim of this study was to evaluate the biomechanical behavior of 5 different fixation materials for the Bilateral Sagittal Split Osteotomy (BSSO) using miniplates and monocortical screws, in a 10-mm advancement and 20º counterclockwise rotation. Fixation materials were adapted bilaterally in the osteotomy site, according to 5 models: Model M1: one straight 4-hole miniplate and 4 monocortical screws; Model M2: two 4-hole straight miniplates and 8 monocortical screws; Model M3: one 10-hole double miniplate with two bridges and 10 monocortical screws; Model M4: one 8-hole 20º angled double miniplate with two bridges and 8 monocortical screws; Model M5: one semi-curve 6-hole miniplate and 6 monocortical screws. Two loading patterns were applied in each model: 100 N load in the posterior region, and 50 N load in the anterior region. Bone segments displacement and highest stress values in plates and screws were recorded. Highest displacement mesurements were recorded in M1 model (1,409 mm), while M2 model recorded lowest values when considering the posterior (0,446 mm) and anterior (0,481 mm) loads; M1 model (1209,2 MPa) recorded the highest stress peaks in screws; M1 (1067,9 MPa) and M3 (1479,2 MPa) recorded the highest stress peaks in plates, while the M5 model recorded the smallest peaks (387,3 MPa). The results suggest that the M1 and M3 models are those with the worst biomechanical behavior, while the M2 model is the most stable, and the M5 model with the best load distribution.